EVALUASI SIKAP SISWA SMP TERHADAP IPA DI KABUPATEN MUARO JAMBI - Dwi Agus Kurniawan; Astalini Astalini; Lika anggraini (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2018)
An attitude is a form of one's perception of an object that is described with expressions of like or not. The purpose of the study was to describe the attitudes of students toward the three indicators of the attitude of the SMP in Muaro Jambi. The research method uses quantitative survey research. The instrument used was a questionnaire that focused on three indicators consisting of 25 statements and also interviews. The sample in this study amounted to 2815 junior high school students in Muaro Jambi. The results of research on three attitude indicators which became the dominant focus of research in the good category. The Social Implications of Science show a good category with a percentage of 53.2%. The pleasure of science learning is well categorized with a percentage of 66.3%. A career interest in science is categorized as enough with a percentage of 41.8%. From the research that has been carried out, it can be seen that the attitude of students in junior high school is categorized as good because the three indicators examined show good categories.